Analyzing Translation Strategies Utilized in the Translation of Song Do You Want to Build a Snowman? - Chrisna Leni; Athriyana Santye Pattiwael (Journal of Language and Literature, 2019)
This study focuses on revealing translation strategies used in the translation of song Do you want to build a snowman? in terms of strategic and non-strategic translation strategies. The data were the lines of a pair English-Indonesian selected song lyrics. The analysis of non-strategic translation strategies and strategic translation strategies was conducted by basing on the framework developed by kerstrm (2009) and Lefevere (1975). This study used qualitative descriptive method in analyzing the data. The result of the study shows that the translator tends to translate lines of the lyrics by using fewer number of words, yet the number of syllables remains similar to the source lines. Regarding strategic translation strategies used by the translator in translating lines of the lyrics, it is found that five strategies out of nine strategies have been used, they are paraphrases, rhymes, interpretation, omission of words, and addition of words strategies. Keywords: Non-Strategic translation strategies, song translation, strategic translation strategies